Abby, tried and true - Gephart, Donna (Simon & Schuster Books for Young Readers, 2021)
Abby Braverman strives to navigate seventh grade without her best friend, keep up her older brother's spirits while he undergoes cancer treatment, and figure out her surprising new feelings for the boy next door. Includes facts about testicular cancer.